Protective Effects of Liraglutide and Linagliptin in C. elegans as a New Model for Glucose-Induced Neurodegeneration - Wongchai, K.; Schlotterer, A.; Lin, J.; Humpert, P. M.; Klein, T.; Hammes, H.-P.; Morcos, M. (Hormone and Metabolic Research, 2016)
Liraglutide and linagliptin are novel drugs for the treatment of diabetes. Antioxidative and neuroprotective effects have been described for both compounds. However, it is not yet known, whether these mechanisms are also protective against diabetic retinal neurodegeneration. We assessed the antioxidative and neuroprotective capabilities of liraglutide and linagliptin as well as the signaling pathways involved, by using C. elegans as a model for glucose-induced neurodegeneration. C. elegans were cultivated under conditions, which mimic clinical hyperglycemia, and treated with 160 μmol/l liraglutide or 13 μmol/l linagliptin. Oxidative stress was reduced by 29 or 78% and methylglyoxal-derived advanced glycation endproducts (AGEs) by 33 or 22%, respectively. This resulted in an improved neuronal function by 42 or 60% and an extended mean lifespan by 9 or 11%, respectively. Antioxidative and AGE reducing effects of liraglutide and linagliptin were not dependent on v-akt murine thymoma viral oncogene homologue 1/forkhead box O1 (AKT1/FOXO). Neuroprotection by liraglutide was AKT1/FOXO dependent, yet AKT1/FOXO independent upon linagliptin treatment. Both liraglutide and linagliptin exert neuroprotective effects in an experimental model for glucose-induced neurodegeneration, however, the signaling pathways differ in the present study. Further pharmacological intervention with these pathways may help to delay the clinical onset of diabetic retinopathy by preserving neuronal integrity.
Keywords: GLP-1; DPP-4; neuroprotective effects; diabetic complications